Distribusi Horizontal Klorofil-a Fitoplankton Sebagai Indikator Tingkat Kesuburan Perairan di Teluk Meulaboh Aceh Barat - Neneng Marlian; Ario Damar; Hefni Effendi (Jurnal Ilmu Pertanian Indonesia, 2015)
The research on horizontal distribution clorophyll-a fitoplankton as indicator the tropic state in waters of Meulaboh Bay conducted on Mei-July 2014 in Meulaboh Bay. Sampling was done using the method of purposive sampling at 10 sites, which consist of river, mouth river, bay waters, and middle of bay to outer of bay. The purpose of this research is to analyse horizontal distribution of clorophyll-a fitoplankton as the tropic state indicator in the waters and to analyse relationship between clorphyll-a fitoplankton with nutrients availability N and P. The result showed that the horizontal distribution pattern of clorophyll-a fitoplankton dominated by the waters near to teresterial land, likes river, mouth river, and edge of bay, afterward its gradually slightly decrease in the middle of bay and lower in outer of bay. High or low of clorophyll-a was due to the influence of nutirent load N and P in the waters of Meulaboh Bay. The tropic states based on abundance clorophyll-a fitoplankton was categorised in the mesotrofic condition.